Mutations of KRAS, NRAS, BRAF, EGFR, and PIK3CA genes in urachal carcinoma: Occurence and prognostic significance - Módos, Orsolya (Oncotarget, 2016)
PURPOSE: Targeted therapy represents an attractive alternative for rare tumors such as urachal carcinoma (UrC). The aim of this study was to assess the mutations of the most commonly affected 5 genes in the targetable EGFR-pathway in UrC and comapre their frequencies to those of found in urothelial and colorectal cancer. MATERIALS AND METHODS: Mutational hot-spots of selected genes were tested in 22 UrC samples by pyrosequencing. Mutational patterns were compared to those published for colorectal and urothelial cancers. Furthermore, we sought correlations between mutations and clinicopathological and follow-up data. RESULTS: We found 11 mutations in 10 of 22 (45%) patients. The most frequently mutated gene was KRAS (27%) followed by BRAF (18%) and NRAS (5%), while no mutations were detected in the EGFR and PIK3CA genes. No correlation was found between the mutation status and clinicopathological parameters (Sheldon/Mayo stage, tumor grade, metastases). Furthermore, none of the mutations correlated with progression-free or overall survival. CONCLUSIONS: The mutation pattern of UrC is more similar to colorectal than to urothelial cancer. However, the mutation characteristics of UrC seems to be unique suggesting that clinical decision-making for UrC cannot be simply adopted from urothelial or colorectal carcinoma. The high occurence of EGFR-pathway mutations warrants the testing for KRAS and BRAF mutations when considering anti-EGFR therapy in UrC.